ORGANIZATION OF SMALL BUSINESS SUPPORT INFRASTRUCTURE AND MEDIUM-SIZED BUSINESSES AT THE REGIONAL LEVEL - Evdokimova E. K., Gordova V. V. (Socio-Economic Processes of Modern Society (for the 80th anniversary of Lev Panteleimonovich Kurakov), 2023)
the article considers the need to organize a support infrastructure in order to ensure the stable functioning of small and medium-sized businesses. The problems of the development of small and medium-sized businesses are outlined. The main objects of the support infrastructure in the Kemerovo region are shown.
Keywords: регион; region; меры поддержки; small and medium-sized enterprises; малое и среднее предпринимательство; инфраструктура поддержки; support measures; support infrastructure